A decentralized group signature scheme for privacy protection in a blockchain - Devidas, Sabavat; Rao, Subba Y.V.; Rekha, Rukma N. (Zielona Góra: Uniwersytet Zielonogórski)
Group signature schemes play a vital role in protecting identity privacy of a member of a group who signs a message using the group signature. However, in the existing group signature schemes the centralized group manager has control over all the participants, and these managers can be malicious. They may take a biased decision when there is a dispute among the group members or while revealing the identity of a group member.
Keywords: blockchain; decentralization; e-auction; group signature; privacy; smart contract